1991
DOI: 10.1002/ppul.1950110314
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effect of high‐frequency chest compression therapy on pulmonary complications of cystic fibrosis

Abstract: A high-frequency chest compression (HFCC) device for clearance of mucous secretions from airways was tested in 16 cystic fibrosis (CF) patients with significant improvement in pulmonary function for the HFCC period, which averaged 22 months per patient. The device consists of a variable air pulse delivery system and a non-stretch inflatable vest worn by the patient to cover the entire torso. The patients perform 30 minute therapy sessions divided into 5 minute periods at each of six frequencies. Individual pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(40 citation statements)
references
References 13 publications
2
34
0
4
Order By: Relevance
“…This finding concurs with Warwick et al, 23 who found that long-term (7-26 months) of HFCWC significantly changed toward positivity the negative slope of lung function parameters in children with cystic fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…This finding concurs with Warwick et al, 23 who found that long-term (7-26 months) of HFCWC significantly changed toward positivity the negative slope of lung function parameters in children with cystic fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…Physical techniques such as breath stacking and assisted cough, as well as medication management (bronchodilators, anticholinergic agents), have become increasingly common in aggressive multidisciplinary treatment settings. In addition, use of intrasalivary gland injection of botulinum toxin has been shown to result in significant improvement of sialorrhea and improve respiratory insufficiency [130,131].…”
Section: Respiratory Therapiesmentioning
confidence: 99%
“…Эффективность метода ВЧКГС продемонстриро вана у пациентов с муковисцидозом [16][17][18][19], брон хоэктатической болезнью [20] и при стабильном течении тяжелой ХОБЛ [21]. Однако данные о воз можности использования ВЧКГС при обострении ХОБЛ практически отсутствуют.…”
unclassified